Investigation of the SPINK1 N34S mutation in Romanian patients with alcoholic chronic pancreatitis: a clinical analysis based on the criteria of the M-ANNHEIM classifi cation - Diaconu, Brindusa L.; Ciobanu, Lidia; Mocan, Teodora; Pfützer, Roland; Scafaru, Marius P.; Acalovschi, Monica; Singer, Manfred V.; Schneider, Alexander (Journal of gastrointestinal and liver diseases, 2009)
Background and aims: The N34S mutation in the serine protease inhibitor Kazal type I (SPINK1) gene has been associated with chronic pancreatitis. Clinical data about the phenotypic expression of alcoholic chronic pancreatitis with the N34S variant are limited. The prevalence of the N34S mutation in patients with chronic pancreatitis and healthy individuals from Eastern Europe is unknown.Methods: We studied Romanian patients with chronic pancreatitis and investigated the clinical presentation in patients with N34S mutation. The SPINK1 N34S variant was analysed in 94 chronic pancreatitis patients and 96 healthy controls by an allele specific PCR method and a restriction fragment length polymorphism method. A meta-analysis was conducted with previous N34S association studies. The clinical course of alcoholic pancreatitis was evaluated according to the severity criteria of the M-ANNHEIM classification system of chronic pancreatitis.Results: A heterozygous N34S mutation was found in 1 of 96 healthy individuals (1%) and in 4 of 80 patients (5 %) with alcoholic chronic pancreatitis. The meta-analysis confirmed the status of N34S as a risk factor for the development of alcoholic chronic pancreatitis (OR=5.3). However, the clinical course of the disease was similar in patients with and without N34S mutation.Conclusion: The N34S mutation is a weak risk factor for alcoholic chronic pancreatitis.